To Be Unfree : Republicanism and Unfreedom in History, Literature, and Philosophy - Dahl, Christian; Andersen Nexø, Tue (2014)
To Be Unfree is a collection of essays investigating how political unfreedom has been and can be articulated within the republican tradition of political thought. The book combines a theoretical discussion of how freedom and its opposites have been conceptualized in the republican tradition with a broader perspective on this tradition's impact on the representation of unfreedom in Western literature and cultural history. It thus complicates our understanding of what it means to be unfree and unveils a series of distinctions which also shape our modern notions of freedom.